SMEs in Indonesia: How do market and entrepreneurial approaches shape dynamic capabilities and performance? - Cahaya, Yohanes Ferry; Prasetyo, Johan Hendri; Winarti, Ch Endah; Erasashanti, Annathasia Puji; Rachman, Hikmah Abdul (Edelweiss Applied Science and Technology, 2024)
This study delves into the impact of market orientation and entrepreneurship on dynamic capabilities and SME performance within the Culinary SME sector of West Java Province, Indonesia. The study utilized a quantitative-causal research methodology to gather data from a sample of 420 Culinary (SMEs) that had been operating for a minimum of 5 years. The acquired data was then subjected to analysis using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate significant potential for market orientation and entrepreneurship to bolster dynamic capabilities and subsequently enhance SME performance. Furthermore, the study found that dynamic capabilities positively influence SME performance. Importantly, the study identifies an indirect pathway through which market orientation and entrepreneurship can augment SME performance by leveraging dynamic capabilities as a mediator. Practical implications emphasize the critical importance for Culinary SMEs to cultivate robust market orientation, harness entrepreneurial potential for strategic risk-taking and innovation, and fortify dynamic capabilities. Strengthening these facets enables SMEs to effectively translate market insights into actionable strategies, thereby fostering sustainable growth in a competitive business landscape. In essence, this research provides valuable insights into the interplay of market orientation, entrepreneurship, dynamic capabilities, and SME performance, offering actionable guidance for Culinary SMEs in West Java Province and beyond to navigate challenges and capitalize on opportunities for sustainable development and competitiveness.